1982
DOI: 10.3354/meps007207
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction by Fragmentation in Corals

Abstract: Production of new colonies by fragmentation of established colonies is shown to be an extremely important mode of reproduction and local distribution anlong major reef-bu~lding corals. This type of reproduction avoids the high mortality rates of larvae and juveniles and spreads the risk of mortality for the genotype Fragmentation by corals wlth high growth rates results In their domination of certain reef zones, rapid growth of reefs on which these corals are abundant, and rapid recovery from disturbances. I c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
424
1
13

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(449 citation statements)
references
References 65 publications
8
424
1
13
Order By: Relevance
“…Little is known about the demography of mushroom corals (e.g., Highsmith 1982;Fadlallah 1983;Harrison 1985;Richmond 1987;Hoeksema 1989). The size-frequency and size-cover patterns of extraordinarily large colonies (14%'71 cm diameter) on the bioherm were unprecedented as was the fungiid diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the demography of mushroom corals (e.g., Highsmith 1982;Fadlallah 1983;Harrison 1985;Richmond 1987;Hoeksema 1989). The size-frequency and size-cover patterns of extraordinarily large colonies (14%'71 cm diameter) on the bioherm were unprecedented as was the fungiid diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Modular organisms, such as scleractinians, octocorals, bryozoans and crustose coralline algae often not only have long lifespans but also reproduce asexually 60,61 , which may result in exceptional lifespans of the genotype compared to other organisms 60,62 , a feat only possible via substantial environmental tolerance or phenotypic plasticity 63 . Importantly, since such old colonies tend to be large and therefore highly fecund 64 , they can potentially hinder genetic adaptation of the population by swamping the gamete pool with genotypes that are no longer a good match to the local environment.…”
Section: Predictors Of Tgp In Coralsmentioning
confidence: 99%
“…An increasing amount of work has documented the timing and mode of coral reproduction, the recruitment of juveniles on artificial and natural substrates and the behavior of coral planulae in the laboratory (see reviews by Highsmith 1982 andFadlallah 1983). The calorimetric work of Richmond (1982) has demonstrated that the century-old assumption that coral planulae are capable of dispersing over long distances (Semper 1881, Vaughan 1907, is at least energetically justified in certain species.…”
Section: Introductionmentioning
confidence: 99%